(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
The success of spawning determines the availability of gonggong conch seeds. The purpose of this study was to analyze the effectiveness of different types of hormones namely ovaprim® and hCG in stimulating the spawning of gonggong conch. Eighty-four pairs of broodstock were injected according to the design with ovaprim® or hCG, or combination of both hormones at a dose of 0.5 µL/g BW. Post-injection broodstock are spawned in an aquarium with a density of 7 pairs per aquarium. The observed parameters were the number of spawned broodstocks, the number of released eggs, the latency time, and the histological of the broodstock gonads. The Kruskal Wallis test was used to analyze the number of spawned broodstock, and the analysis of variace (ANOVA) was used to analyze the number of released eggs. The results showed that there was no significant differences between the treatments (P>0.05) on the number of spawned broodstocks, but hCG administration gave the highest number of spawned broodstocks (52.38%). The latency time of broodstock spawned generally began on the 2nd and 3rd day after 0.5 µL/g BW ovaprim administration. Based on the percentage of spawned broodstock and the value of all observation parameters, it was concluded that the hCG with a dose of 0.5 µL/g BW (P1) gives a better response than the other treatments.